Impact of adjuvant chemotherapy delay on overall survival in early-stage breast cancer: a retrospective analysis - Alhalabi, Ahmad; Abdo, Theresa; Herrán, María; Sarna, Kaylee; Tfayli, Rami; Nahleh, Zeina (Frontiers in Oncology, 2025)
BackgroundIn Early-Stage Breast Cancer (EBC), there is no clear consensus on the ideal window for initiation of adjuvant chemotherapy from the time of definitive surgery. Furthermore, there is a paucity of data on the effectiveness of late chemotherapy. Herein, we aim to assess the effect of delays in adjuvant chemotherapy on overall survival (OS) and to investigate whether there could be a role and remaining effectiveness of late adjuvant chemotherapy compared to no chemotherapy.MethodsA retrospective cohort study was conducted utilizing data from the National Cancer Database (NCDB), focusing on patients with EBC from 2010 to 2020. Univariate and multivariate Cox regression analyses were employed. Propensity score matching (PSM) (1:1) was performed between the late and no chemotherapy groups to balance baseline characteristics.ResultsN = 326,322 female patients, with a median age of 55 years (Range 47.0-62.0), were identified. Patients were distributed as follows in Group 1 (Adjuvant Chemo < 2 months since surgery N = 266,185, 81.6%), Group 2 (Adjuvant Chemo 2-4 months N = 55,063, 16.9%), Group 3 (Adjuvant Chemo 4-6 months n = 3,749, 1.15%), and Group 4 (Adjuvant Chemo given > 6 months N = 1,325, 0.4%). Multivariate analysis showed that patients in Groups 2,3,4 had worse OS compared to Group 1 (HR 1.28, 95% CI 1.20-1.36, p<0.0001; HR 1.53, 95% CI 1.27-1.84, p<0.0001; and HR 1.46, 95% CI 1.09-1.96, p=0.0104, respectively), indicating that the ideal period to start chemotherapy is within the first 2 months after surgery. When comparing the Late chemotherapy (Group 4) versus a Control Group of patients who declined recommended adjuvant chemotherapy, multivariate analysis indicated that patients in the control group experienced significantly worse OS compared to the late chemotherapy group (HR 1.55, 95% CI 1.13-2.14, p = 0.006).ConclusionSystemic adjuvant chemotherapy given within < 2 months period since definitive surgery provides an optimal survival advantage. Notably, patients receiving late adjuvant chemotherapy > 6 months can still derive some benefit compared to those without treatment, making it a viable, though suboptimal, treatment option.